Soziologie in interdisziplinären Netzwerken - Amann, Anton (2005)
Extensive considerations are imperative to address the increasingly urgent social and cultural issues that national societies encounter within the process of emergent global expansion. With respect to sociology, this requirement applies to images of disciplinary self-conception and the formulation of scientific tasks, to relationships with other disciplines, with politics and practice. Likewise, it relates to what has been seen to give meaning to the theoretically and methodically established delimitations of object spaces and research areas. Not least, such issues impact the societal role adopted by the social sciences, associated over the past two decades with the notion of scientific "crisis". The issues that bridge the discussions of such transitions in the present anthology refer to the entwinements of theory and empirical work, ageing and generational research, areas of development studies and internationalization. They also deal with the life course and quality of life, the gender division of labor, health and prevention, as well as epidemiological and ethnological-sociological case studies in Africa. Quite simply, we are coming to perceive a transitional situation in various respects. Taking up the above transitional perspectives, authors from Great Britain, France, Germany and Austria - including C. Attias-Donfut, U. Beck, M. Kohli, M. Johnson, U. Lehr, L. Rosenmayr and others - develop analyses and suggestions that serve to determine anew the role of interdisciplinarity in sociology. These scholars have identified a substantial deficiency in theory, accompanied by bursting quantities of detailed empirical material in various fields of research, and propose to realign research objectives. The broad perspectives plotted in this volume provide the grounds for further scientific debate.